Transcranial Direct Current Stimulation Does Not Affect Sprint Performance or the Horizontal Force-Velocity Profile. Issue 3 (3rd July 2022) - Alix-Fages, Carlos; Garcia-Ramos, Amador; Romero-Arenas, Salvador; Nadal, Giancarlo Calderón; Jerez-Martínez, Agustín; Colomer-Poveda, David; Márquez, Gonzalo
ABSTRACT: Purpose : The aim of this study was to explore the effects of transcranial direct current stimulation (tDCS) on sprint performance and the horizontal force-velocity (F-v) profile. Method : Thirty-two healthy subjects (25 men and 7 women; age = 21.8 ± 2.4 years) completed three sessions separated by 1 week following a double-blinded crossover design. Each session consisted of two maximal sprints of 30 meters that were performed after applying ANODAL, CATHODAL or SHAM tDCS over the left dorsolateral prefrontal cortex (DLPFC) for 15 minutes at 2 mA. The 30-m time and the horizontal F-v profile variables (theoretical maximal force [ F 0 ], theoretical maximal velocity, Fv slope, maximal power [Pmax], decrease in the ratio of horizontal-to-resultant force, and maximal ratio of horizontal-to-resultant force) were compared between the tDCS conditions. Results : No significant differences between the tDCS conditions were observed for any variable ( p range = 0.061 to 0.842). The magnitude of the differences was negligible for most of the comparisons (effect size [ES] < 0.20) with the only exception of Pmax and F 0 which were greater for the ANODAL compared to the SHAM condition (both ES = 0.20). Conclusions : The application of tDCS over the DLPFC is not effective to increase non-fatigued sprint performance.